IMPROVING THE DESIGN OF THE BODIES OF PASSENGER CARS FOR HIGH-SPEED TRANSPORTATION - Prykhodko, V. I.; Shkabrov, O. O.; Myamlin, S. V.; Yagoda, P. O. (Science and Transport Progress, 2007)
The article offers some options of improving design and reducing the weight of passenger car bodies and develops a mathematical model for studying the strained-deformed state of the body. Some practical results have been presented.